Analysis Of Cape Index And Total Index Thresholds Towards Cumulonimbus Cloud And Thunderstorm Events At Minangkabau International Airport - Indah Yoseva Effendi; Nofi Yendri Sudiar; Ratnawulan; Harman Amir (Journal of Climate Change Society, 2026)
Indonesia located along the equator and dominated by oceanic areas, is highly vulnerable to atmospheric dynamics and extreme convective weather. Minangkabau International Airport (BIM), situated in a coastal region of West Sumatra, is frequently affected by cumulonimbus (Cb) clouds and thunderstorms (TS), which pose risks to aviation safety. This study aims to determine the threshold values of the Convective Available Potential Energy (CAPE) index and the Total Totals Index (TT) that are appropriate for local conditions, based on radiosonde and synoptic observation data from 2019–2023, and verified using 2024 data. The CAPE and TT values were analyzed using Sturges’ method to determine frequency intervals and dichotomous analysis to establish threshold effectiveness. Results indicate that CAPE thresholds for Cb clouds range from 495 to 2679 J/kg, while TT thresholds for thunderstorms range from 43.5 to 47.4, depending on the seasonal variation (DJF, MAM, JJA, SON). These thresholds demonstrated strong performance in identifying convective weather events, thus serving as a useful reference for forecasting and enhancing flight safety at BIM.